Data for "Athabasca River avulsion underway in the Peace-Athabasca Delta, Canada" ... - Wang, Bo; Kyzivat, Ethan; Gleason, Colin; Fayne, Jessica V.; Harlan, Merritt E.; Langhorst, Theodore; Dongmei Feng; Eidam, Emily; Peters, Daniel L.; Ishitsuka, Yuta; Wayana Dolan; Tamlin M. Pavelsky; et al. (Zenodo, 2023)
Water surface elevation, river depth, and ADCP data for paper "Athabasca River avulsion underway in the Peace-Athabasca Delta, Canada, Water Resources Research , Wang et al. 2023". ...